2018
DOI: 10.1128/aem.01273-17
|View full text |Cite
|
Sign up to set email alerts
|

Sulfolobus acidocaldarius Transports Pentoses via a Carbohydrate Uptake Transporter 2 (CUT2)-Type ABC Transporter and Metabolizes Them through the Aldolase-Independent Weimberg Pathway

Abstract: possess a great metabolic versatility and grow heterotrophically on various carbon sources such as different sugars and peptides. Known sugar transporters in Archaea predominantly belong to ABC transport systems. Although several ABC transporters for sugar uptake have been characterized in the crenarchaeon , only one homologue of these transporters, the maltose/maltooligomer transporter, could be identified in the closely related Comparison of the transcriptome of grown on peptides alone and peptides in presen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

3
47
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 33 publications
(50 citation statements)
references
References 46 publications
3
47
0
Order By: Relevance
“…It is revealed that this pentose transporter is the first identified ABC transporter of the carbohydrate uptake transporter-2 (CUT2) family in the domain of Archaea. In addition, the growth defect on d-xylose in the single-gene deletion mutants of ABC transporter further illustrated the importance of this transport system [22]. Sulfolobus solfataricus and the closely related Sulfolobus acidocaldarius are the best-studied organisms in the phylum of crenarchaeota for sugar transport, and a number of sugar ABC transporters have been identified and examined [23,24].…”
Section: Native Xylose Transportersmentioning
confidence: 99%
See 1 more Smart Citation
“…It is revealed that this pentose transporter is the first identified ABC transporter of the carbohydrate uptake transporter-2 (CUT2) family in the domain of Archaea. In addition, the growth defect on d-xylose in the single-gene deletion mutants of ABC transporter further illustrated the importance of this transport system [22]. Sulfolobus solfataricus and the closely related Sulfolobus acidocaldarius are the best-studied organisms in the phylum of crenarchaeota for sugar transport, and a number of sugar ABC transporters have been identified and examined [23,24].…”
Section: Native Xylose Transportersmentioning
confidence: 99%
“…Sulfolobus solfataricus and the closely related Sulfolobus acidocaldarius are the best-studied organisms in the phylum of crenarchaeota for sugar transport, and a number of sugar ABC transporters have been identified and examined [23,24]. Besides those ABC transporters, only the MFS transporter for glucose and PTS system for d-fructose were characterized in Haloferax volcanii and Haloarchaea, respectively [22].…”
Section: Native Xylose Transportersmentioning
confidence: 99%
“…1a) has gained major attention 8 . The pathway has been identified in several bacteria and archaea [9][10][11][12] , and is best understood for the oligotrophic freshwater bacterium Caulobacter crescentus, in which the involved enzymes are encoded in the D-xylose-inducible xylXABCD operon (CC0823-CC0819) 13 (Fig. 1b).…”
mentioning
confidence: 99%
“…Although the first and second metabolic pathways are phosphorylative pathways, the third pathway, found in bacteria and archaea, is partially equivalent to the nonphosphorylative Entner-Doudoroff pathway [5]. metabolism, in which L-KDP is converted to pyruvate and glycolaldehyde (Route I) [6,7], a-ketoglutarate (Route II) [8][9][10][11], or pyruvate and glycolate (Route III) [12]. L-Arabino-c-lactone is then converted to L-2-keto-3deoxypentonate (L-KDP) by L-arabinonolactonase (EC 3.1.1.15) and L-arabonate dehydratase (EC 4.2.1.25).…”
mentioning
confidence: 99%
“…metabolism, in which L-KDP is converted to pyruvate and glycolaldehyde (Route I) [6,7], a-ketoglutarate (Route II) [8][9][10][11], or pyruvate and glycolate (Route III) [12].…”
mentioning
confidence: 99%